2022
DOI: 10.1088/1361-6528/aca7cb
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nano-sieves by femtosecond laser irradiation

Abstract: The formation of nano-pores in graphene crystal structure is alternative way to engineer its electronic properties, chemical reactivity, and surface interactions, enabling applications in technological fields such as sensing, energy and separation. The past few years, nano-perforation of graphene sheets has been accomplished by a variety of different methods suffering mainly from poor scalability and cost efficiency issues. In this work, we introduce an experimental protocol to engineer nanometer scale pores i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 90 publications
(124 reference statements)
1
9
0
Order By: Relevance
“…[7][8][9] In multi-pulse irradiation, the ablation threshold decreases due to a cumulative effect, 10 and the reported threshold fluence varies in a wide range, being around 57, 19.1, and 3.85 mJ/cm 2 , which evidences the strong dependence of this value on the experimental conditions. 1,11,12 Below the ablation threshold, fs-laser irradiation induces the nonthermal local alteration of graphene: Roberts et al reported the formation of defects and, additionally, p-type doping due to the binding of the atmospheric oxygen to the dangling bonds of the fragmented lattice 7 ; Vasquez et al reported creation of defects at fluences around 80% of the ablation threshold 12 ; Pettersson's group extensively reported the formation of oxidized nano-islands by irradiation under air conditions 3,13,14 and optical forging of the graphene surface in inert atmosphere. 15,16 Recently, Katsiaounis et al reported the formation of concentric areas with the inner one formed by a network of nanopores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In multi-pulse irradiation, the ablation threshold decreases due to a cumulative effect, 10 and the reported threshold fluence varies in a wide range, being around 57, 19.1, and 3.85 mJ/cm 2 , which evidences the strong dependence of this value on the experimental conditions. 1,11,12 Below the ablation threshold, fs-laser irradiation induces the nonthermal local alteration of graphene: Roberts et al reported the formation of defects and, additionally, p-type doping due to the binding of the atmospheric oxygen to the dangling bonds of the fragmented lattice 7 ; Vasquez et al reported creation of defects at fluences around 80% of the ablation threshold 12 ; Pettersson's group extensively reported the formation of oxidized nano-islands by irradiation under air conditions 3,13,14 and optical forging of the graphene surface in inert atmosphere. 15,16 Recently, Katsiaounis et al reported the formation of concentric areas with the inner one formed by a network of nanopores.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recently, Katsiaounis et al reported the formation of concentric areas with the inner one formed by a network of nanopores. 11 Raman spectroscopy was a fundamental characterization technique in the above studies. The Raman spectrum of pristine graphene consists of two distinct bands: the G band at $1587 cm À1 , given by a first-order resonant Raman process involving a phonon with zero wavevector, and the 2D band at $2705 cm À1 , given by two phonons with opposite wavevectors.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving accurate control and high reproducibility of graphene masks requires reliable patterning techniques, such as lithography. An attractive possibility to pattern graphene lies in using the ultrafast lasers [ 16 , 17 ]. Being contactless, this method reduces undesired modification of graphene, while due to its limited thermal influence, it can be applied for patterning graphene on sensitive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 In a very recent study, large numbers of nanopores were generated in monolayer graphene on a Si/SiO 2 wafer using a high-repetition-rate femtosecond-laser irradiation. 38 They state that atomic force microscopy (AFM) is a reliable method for characterizing the nanopores formed, whereas its validity for the self-suspended membrane remains to be examined. In this study, we explored the feasibility of creating sub-100 nm holes in self-suspended monolayer graphene using femtosecond-laser processing.…”
mentioning
confidence: 99%
“…Recently, Alaghemandi et al simulated the atomic dynamics in graphene under femtosecond-laser irradiation and demonstrated the formation of atomic-level defects as well as nanopores . Atomic defects in the crystal structure of graphene enhance chemical reactivity and can be utilized to locally functionalize graphene membranes by attaching arbitrary chemical groups to the defect vacancy. , The defects also affect the electronic structure of graphene and thus have potential applications in high-performance electronics materials and in innovative technologies such as valleytronics. , In a very recent study, large numbers of nanopores were generated in monolayer graphene on a Si/SiO 2 wafer using a high-repetition-rate femtosecond-laser irradiation . They state that atomic force microscopy (AFM) is a reliable method for characterizing the nanopores formed, whereas its validity for the self-suspended membrane remains to be examined.…”
mentioning
confidence: 99%